All-polyethylene versus metal-backed tibial components in total knee arthroplasty: a meta-analysis of randomized controlled trials - Aissam Elmhiregh (14150667) (2023)
Objectives The design of tibial trays for total knee arthroplasty (TKA) has been a topic of research for several decades. Although all-polyethylene trays were developed to address issues such as osteolysis and to enhance the longevity of the prosthesis, as well as knee range of motion, metal-backed designs have remained the most commonly used type of prosthesis. This meta-analysis aimed to compare the clinical, radiological, and survival outcomes of both designs. Methods Five databases were searched from inception until October 1, 2020, for randomized controlled trials (RCTs) that compared the outcomes of all-polyethylene and metal-backed tibial components in TKA. The outcomes of interest included range of motion, knee society score, stairs climbing scores, radiostereographic analysis, survivorship and complication. This review was conducted in line with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Risk of bias was assessed using the Newcastle–Ottawa tool. Results A total of 14 RCTs with 1367 TKA were included with a mean age of – years and – years for all-polyethylene and metal-backed tibial components groups, respectively. All-polyethylene group demonstrated statistically significant differences in five-year survivorship (OR 0.27; 95% CI 0.10–0.75; p value 0.01) and stairs climbing score (OR − 2.07; 95% CI − 3.27–0.87; p value 0.0007) when compared to the metal-backed group. The metal-backed design was significantly more radiographically stable in anterior–posterior, varus–valgus, and internal–external rotations at the 2-year follow-up compared to all-polyethylene tibias (OR − 0.09; 95% CI − 0.16 to − 0.02; p value 0.02) as per the pooled radiostereographic analysis. However, ten-year survivorship (OR 0.92; 95% CI 0.53–1.60; p value 0.78), range of motion (OR − 0.57; 95% CI − 2.00–0.85, p value 0.43), knee society scores (OR 1.38; 95% CI − 0.47–3.23, p value 0.14), and complications (OR 0.83; 95% CI 0.5–1.39, p value 0.48) were comparable between both groups. Conclusions While this meta-analysis suggests that all-polyethylene tibial components in total knee arthroplasty may offer advantages over metal-backed components in terms of five-year survivorship, and stairs climbing score, this finding should be considered in the context of potential confounding factors. Nonetheless, based on the results, the all-polyethylene implant should be considered a viable choice for primary knee replacement. Level of evidence I. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-023-03594-y Additional institutions affiliated with: Surgical Specialty Center - HMC